Kinetic of peroxide index variation and shelf life of mayonnaise with microencapsulated oregano essential oil - Rojas-Molina, Jaime O. (2025)
This work aimed to evaluate the influence of adding microencapsulated oregano (Origanum vulgare L.) essential oil (MOEO) on the stability of mayonnaise. Three formulations were developed with MOEO at different concentrations (0.0, 0.26, and 0.44%). Mayonnaises were stored at 35, 45, and 55 ºC until deterioration. The titratable acidity and peroxide index (PI) were determined during the accelerated storage. PI was subjected to linear regression analysis as a function of time. The parameters of the Arrhenius model (k and Ea) for the variation of PI and the temperature acceleration factor (Q10) were also determined. Mayonnaise, with 0.44% MOEO, presented the highest stability in delaying the increase in the PI, indicating the deterioration of this type of product. In all cases, the PI variation was adjusted to a zero-order reaction. Linear models were obtained to estimate the shelf life of mayonnaises.